2022
DOI: 10.1128/spectrum.02441-21
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Inhibit Methicillin-Resistant Staphylococcus aureus by Inducing Hydroxyl Radical-Mediated Apoptosis-Like Cell Death

Abstract: The widespread use of antibiotics has led to the emergence of drug-resistant bacteria, particularly multidrug-resistant bacteria. MRSA is the most common drug-resistant bacterium that causes suppurative infections in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…3N ). Increased expression of qoxC and qoxD suggests reduced electron supply to the oxidative respiratory chain, and the decreased expression of AZR indicates compromised electron supply to the oxidative respiratory chain ( 29 , 41 43 ) .These results provide evidence that K. pneumoniae suffered oxidative stress following platelet- K. pneumoniae coculture supernatant treatment.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…3N ). Increased expression of qoxC and qoxD suggests reduced electron supply to the oxidative respiratory chain, and the decreased expression of AZR indicates compromised electron supply to the oxidative respiratory chain ( 29 , 41 43 ) .These results provide evidence that K. pneumoniae suffered oxidative stress following platelet- K. pneumoniae coculture supernatant treatment.…”
Section: Resultsmentioning
confidence: 69%
“…Antibiotic treatment can induce cell apoptosis and cause the targeted cells to exhibit characteristic markers of apoptosis, including phosphatidylserine (PS) exposure, chromosome condensation, and DNA fragmentation ( 29 , 39 ). We found that the platelet- K. pneumoniae coculture supernatant had an antibiotic-like effect on K. pneumoniae in our previous study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a study by Dwyer et al [70] found that bacteria, like eukaryotic cells, possess mechanisms of apoptotic-like death (ALD) under specific stimulation, such as platelets, beetroot extract, and chitooligosaccharides. [71][72][73] Meanwhile, P5CDH plays an important role in cell death. [74] Interestingly, our study revealed that the inhibition of P5CDH activity by celastrol would induce ALD through the accumulation of P5C, which may subsequently lead to cell death.…”
Section: Discussionmentioning
confidence: 99%